PEDAGOGICAL SKILL OF A HIGH SCHOOL TEACHER - Zhytnukhina, Kateryna; Martynjuk, Viktoria (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The scientific and pedagogical activity of a high school teacher is multifaceted, it covers purely teaching activities, scientific research, scientific and methodological work, educational and organizational influence on student youth, self-education. In each of the areas of activity, either the nominal attitude of the teacher to it, or his desire to carry out work at a high level, is manifested. These high requirements for one's own activities, critical thinking, creativity distinguish a teacher with a high level of pedagogical Skill. The relevance of this topic is due to the need to improve pedagogical skills as a component of pedagogical activity, a high degree, perfection and criticality in the activities of a higher school teacher, to determine the skill of a higher school teacher in professional activities, the ability to evaluate and accordingly use knowledge and skills in modern pedagogical situations. The purpose of the study is to reveal the influence of higher education on the formation of pedagogical skills of a teacher. Higher education at the present stage of development of society is called upon to give priority to the formation of students' pedagogical skills as a complex of properties of the teacher's personality, which ensures a high level of self-organization of pedagogical activity; to acquaint with the mechanisms of creative self-realization in professional activity; organize professional and pedagogical activities as a developmental and educational interaction; acquaint with modern pedagogical experience by creating a teacher's portfolio. The methodological basis of the study is the theoretical statements and conclusions of the achievements of the world pedagogical thought, modern concepts and laws of the education system in higher education institutions.